2015
DOI: 10.1007/s13157-015-0674-y
|View full text |Cite|
|
Sign up to set email alerts
|

The Effects of Organic Matter Amendments on Greenhouse Gas Emissions from a Mitigation Wetland in Virginia’s Coastal Plain

Abstract: There is concern that widespread restoration and/or creation of freshwater wetlands may present a radiative forcing hazard because of the potential for methane (CH 4 ) emissions. Yet data on greenhouse gas (GHG) emissions from restored wetlands are sparse and there has been little investigation into the GHG effects of amending wetland soils with organic matter (OM), a practice used to improve function of mitigation wetlands in the Eastern United States. In this study we measure GHG emissions across an OM gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…The presence of SOC may lead to methane production if soils remain inundated (Martins et al 2017;McNicol et al 2017;Mander et al 2018). Methane emissions could be controlled by reducing the amendment application rate (Lou et al 2007;Winton & Richardson 2015). Another alternative, not yet investigated, would be using an amendment with reduced pH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of SOC may lead to methane production if soils remain inundated (Martins et al 2017;McNicol et al 2017;Mander et al 2018). Methane emissions could be controlled by reducing the amendment application rate (Lou et al 2007;Winton & Richardson 2015). Another alternative, not yet investigated, would be using an amendment with reduced pH.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we expected organic amendments to stimulate redoximorphic feature development. Gray (2010) Methanogenesis was considered in four of the studies from two publications (Ballantine et al 2015;Winton & Richardson 2015). The score for methanogenesis alone was −0.75, a potential negative side effect of adding organic amendments.…”
Section: Anaerobic Processesmentioning
confidence: 99%
“…Therefore, we limit the scope of this paper to the effects we observed on CH 4 reliability. CH 4 flux estimates at the CCW (described in detail in Winton and Richardson 2015) range from below detection limits to as high as approximately 5 mg m -2 h -1 .…”
Section: Methodsmentioning
confidence: 99%
“…This may be related to higher organic matter content and 25 nutrient status and a generally higher microbial biomass. Compared to soils supplied with no or little organic matter/nutrients, soils that have received more organic matter are likely to emit substantially larger amounts of CO 2 (Winton and Richardson, 2015). The availability of organic matter is considered one of the most important factors controlling the production of GHGs in wetlands (Badiou et al, 2011).…”
Section: Relationships Between Co 2 Fluxes and Water And Nutrient Avamentioning
confidence: 99%
“…However, based on the above ground dry biomass estimations made during the summer of 2014, these were approximately 6 fold higher at the SFS (35.51 Mg ha -1 ) compared to the 35 LFS (6.02 Mg ha -1 ), indicating that the nutrients originated from outside the site and were presumably associated with drainage water. Many studies have reported an increase in the release of CO 2 via soil respiration as a result of the increased input of organic matter, particularly in wetlands (Samaritani et al, 2011;Winton andBiogeosciences Discuss., doi:10.5194/bg-2016-522, 2017 Manuscript under review for journal Biogeosciences Published: 3 January 2017 c Author(s) 2017. CC-BY 3.0 License.…”
mentioning
confidence: 99%